2021
DOI: 10.1002/hyp.14091
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the stemflow dynamics and driving factors at both inter‐ and intra‐event scales in a typical subtropical deciduous forest

Abstract: Numerous efforts have been made to understand stemflow dynamics under different types of vegetation at the inter-event scale, but few studies have explored the stemflow characteristics and corresponding influencing factors at the intra-event scale. An in-depth investigation of the inter-and intra-event dynamics of stemflow is important for understanding the ecohydrological processes in forest ecosystems. In this study, stemflow volume (F V), stemflow funnelling ratio (F R), and stemflow ratio (F %) from Quercu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…The upper canopy's bark water storage will influence the generation of branchflows and throughfall drip points (Herwitz, 1987;Van Stan et al, 2021). Along the lower portion of the stem, bark water storage can influence the generation of stemflow (Zhang et al, 2021). To advance understanding of this topic, this study examines vertical variability in bark water storage capacity (and other hydrological parameters) for two common tree species {Norway spruce [Picea abies (L.) Karst.]…”
Section: Introductionmentioning
confidence: 99%
“…The upper canopy's bark water storage will influence the generation of branchflows and throughfall drip points (Herwitz, 1987;Van Stan et al, 2021). Along the lower portion of the stem, bark water storage can influence the generation of stemflow (Zhang et al, 2021). To advance understanding of this topic, this study examines vertical variability in bark water storage capacity (and other hydrological parameters) for two common tree species {Norway spruce [Picea abies (L.) Karst.]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, net rainfall could regulate vegetation physiological-metabolic processes through nutrient enrichment (Levia and Frost, 2003;Zhang et al, 2016;Van Stan et al, 2017;Tonello et al, 2021), ultimately affecting the carbon balance of ecosystems (Chu et al, 2018;Jia et al, 2016). In light of the important role of rainfall partitioning in regulating soil moisture and vegetation patch patterns, investigations of the rainfall partitioning dynamics are imperative for a better understanding of the soil-watervegetation relationships (Molina et al, 2019;Van Stan et al, 2020;H. Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the inter-event studies, a few intra-eventscale studies have been reported, which are essential for a better understanding of soil moisture distribution and the hydrological cycle in arid regions (Levia et al, 2010;Levia and Germer, 2015;Cayuela et al, 2018;H. Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, net rainfall could regulate vegetation physiological metabolic processes through nutrient enrichment (Levia and Frost, 2003;Van Stan II et al, 55 2017), ultimately affecting the carbon balance of ecosystems (Chu et al, 2018;Jia et al, 2016). In light of the important role of rainfall partitioning in regulating soil water dynamics and vegetation patch pattern, investigations of the rainfall partitioning dynamics are imperative for a better understanding of the soil-water-vegetation relationships (Molina et al, 2019;Van Stan II et al, 2020;Zhang et al, 2021a). 60 Studies on rainfall partitioning have been broadly carried out in different climatic zones and various types of vegetation (Magliano et al, 2019a;Gordon et al 2020;Sadeghi et al 2020;Rivera and Van Stan II, 2020;Zhang et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the inter-event studies, a detailed understanding of shrub rainfall partitioning dynamics at the intra-event scale is essential for better understanding of soil moisture distribution and the hydrological cycle in arid regions. To understand the temporal 90 fluctuations of shrub rainfall partitioning and its importance to hydrological processes, data with high temporal resolution are required (Levia et al, 2010;Levia and Germer, 2015;Cayuela et al, 2018;Zhang et al, 2021a). For instance, Zhang et al (2018) found that temporal heterogeneity of rainfall clearly affected the spatiotemporal dynamics of TF of C. korshinskii in arid area of northern China.…”
Section: Introductionmentioning
confidence: 99%